(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The study examines the main factors in the development of audit practice of public procurement in terms of sustainable development and decentralization. Approaches to the reform of socio-economic and politicaladministrative spheres of public procurement taking into account the administrative-territorial reform are formulated. In the area of decentralization, the goals of sustainable development are met, which together constitute the general state policy and are characterized by a separate mission with principles, values, motivation, beliefs and development goals. In the implementation of the strategy of sustainable development is important cumulative effect, which is provided by a synergetic approach, which involves combinations in the modeling of elements, creating new progressive forms of organization with the potential of the whole system. The mission of sustainable development is one of the tasks of territorial units and the public sector, based on the ideology of modern multimedia society and environmental motives, which is a map of long-term plans and goals in anticipation of economic progress, identifying key milestones as benchmarks. The economic, ecological and social directions of transformation of audit practice in accordance with the directions of public procurement in the public sector are highlighted. The conceptual model of the organization of audit activity is generalized - complex support of the public procurement process in order to eliminate the corruption component and imperfection of the Prozorro platform, taking into account the promising innovative opportunities of IT audit. It is proved that auditing is a special form of active interaction of the auditee with the object, with the formation of a conscious image of the expected result, which is achieved through partnership with the purposeful implementation of common tasks that make up the development program.